Parenting styles, self-efficacy and pornography addiction: a correlation study among malaysian higher private educational institution students - Abdul Razak, Nora Adeeb; Che Amat, Muhammad Asyraf (Macrothink Institute, 2023)
Parenting styles are essential to meeting children's developmental needs, enhancing their overall life quality, and ensuring they grow up as responsible and competent adults. Pornography addiction has been examined in numerous studies in relation to parenting styles (authoritative, authoritarian, and permissive); however, there is little information available on Malaysian students attending private universities. The current study analysed the correlation between parenting style, self-efficacy, and pornography addiction among 295 private university students. Students were asked to respond to self-administered online questionnaires. The instruments adopted in this study include the Pornography Addiction Screening Tool, the General Self-Efficacy Scale, and the Parental Authority Questionnaire. The findings showed that there are significant relationships between parenting styles, self-efficacy, and pornography addiction. Further analysis of Spearman’s correlation found positive and statistically significant relationships between both fathers’ and mothers’ authoritarian and permissive parenting styles and pornography addiction. The correlation between both fathers’ and mothers’ authoritative parenting styles and pornography addiction was negligible and statistically insignificant. The relationship between fathers’ parenting styles and pornography addiction was weaker compared to mothers’. Self-efficacy had a significant and positive correlation with pornography addiction. This study suggests that parenting styles and self-efficacy are crucial criteria for early psychological growth, with self-efficacy increasing students’ confidence to strive in chosen activities and resist destructive behaviours. Implications for university educators and counsellors, academicians, community leaders, and lawmakers are highlighted to help overcome the growing addiction to pornography among Malaysian youths, particularly at the university level.